The Construction of Symbolic Meaning in the Lyrics of “Bingung” by Iksan Skuter: A Semiotic Analysis - Nandito Dwi Anugrah; Fadhillah Arrizky Heriansyah; Khaerudin Imawan (Athena: Journal of Social, Culture and Society, 2025)
Music plays a significant role in conveying social criticism through meaningful lyrics. This study aims to analyze the construction of symbolic meaning in the lyrics of the song Bingung by Iksan Skuter using Ferdinand de Saussure’s semiotic approach. Employing qualitative interpretive methods, the research uses lyric analysis and audience interviews to understand how listeners interpret the song’s message. Analysis of the lyrics reveals various symbols in Bingung representing social injustice, stereotypes, commercialized education, media manipulation, and the existential paradoxes of modern humanity. The song highlights how individuals often experience labeling, social pressure, and inequality across multiple aspects of life. The semiotic approach reveals that the signifiers in the lyrics represent a complex social reality, while the signified conveys criticism of prevailing social conditions. Therefore, the song serves not only as artistic expression but also as a powerful tool for social critique. This study reinforces the understanding that music can serve as a powerful communication medium for raising social awareness, particularly through works by independent musicians such as Iksan Skuter.